A look into a wormy friend: the model of Caenorhabditis elegans - Lombardo, José Francisco (2021)
This mini-review aims to be a glimpse into the widely used model Caenorhabditis elegans, a free-living nematode found in nature. As the information around this worm is vast and it cannot be summarized in these few lines we will try to introduce its main features, the interest to work with it, and how to begin the journey to incorporate it into your laboratory.